Exercise Testing for Primary Care and Sports Medicine Physicians - Evans, Corey H.; White, Russell D. (Springer New York : Imprint: Springer, 2009)
This practical book is a guide to the exercise stress test performed to determine a patient's risk of developing coronary heart disease. Edited by Drs. Corey H. Evans and Russell D. White, the text is ideal for primary care, family medicine and sports medicine physicians, sports physiologists and trainers. Sections are devoted to performing the exercise stress test, test interpretation and application, and sports medicine applications. Additionally, common abnormal responses and risk stratification of symptomatic and asymptomatic patients are detailed, and flow charts and algorithms bolster the decision-making process. With its straightforward presentation of key material, this text is a welcome resource for those caring for athletes and patients at risk for heart disease.